A Phase Ib Study of Safety and Pharmacokinetics of Ramucirumab in Combination With Paclitaxel in Patients With Advanced Gastric Adenocarcinomas. (17th April 2015) - Ueda, Shinya; Satoh, Taroh; Gotoh, Masahiro; Gao, Ling; Doi, Toshihiko
Abstract : Lessons Learned: The pharmacokinetic results of this phase Ib study of ramucirumab combined with paclitaxel as second‐line therapy in Japanese patients with metastatic gastric or gastro‐esophageal junction adenocarcinoma are in line with previous ramucirumab studies. This combination at the doses and schedule given did not result in any dose‐limiting toxicities and appeared to be safe and well tolerated. Background: This phase Ib study evaluated the tolerability and pharmacokinetics of ramucirumab, an anti‐VEGFR‐2 antibody, combined with paclitaxel as second‐line therapy in Japanese patients with metastatic gastric or gastroesophageal junction adenocarcinoma after first‐line therapy with fluoropyrimidines and/or platinum. Methods: Patients received ramucirumab 8 mg/kg on days 1 and 15 and paclitaxel 80 mg/m 2 on days 1, 8, and 15 of a 28‐day cycle. Safety analyses included all patients ( n = 6). Results: No dose‐limiting toxicities occurred in the first cycle. All patients experienced ≥1 treatment‐emergent adverse event (TEAE); 5 patients experienced grade ≥3 TEAEs. There were two deaths caused by disease progression. The best overall responses were stable disease ( n = 5) and partial response ( n = 1). Patients received ramucirumab and paclitaxel for a median of 12.5 weeks (range: 11.4–42.7 weeks) and 12.2 weeks (range: 11.0–41.0 weeks), respectively. Following a single dose of ramucirumab IV infusion 8 mg/kg, clearance was ∼0.017 L/hour, half‐life ( t 1/2 ) was 138 to 225 hours, and steady‐state volume of distribution ( V ss ) was ∼3 L. Conclusion: The ramucirumab/paclitaxel combination appears to be well‐tolerated in Japanese patients with advanced gastric adenocarcinomas. These results are in line with previous ramucirumab pharmacokinetic studies as anticipated. Abstract : 摘要 背景 . 本项Ib期研究纳入了患有转移性胃腺癌或胃食管交界部腺癌的日本患者，评价了抗VEGFR‐2抗体雷莫芦单抗联合紫杉醇作为氟尿嘧啶和/或铂类一线治疗失败后的二线治疗的耐受性和药代动力学特征。 方法 . 给予患者雷莫芦单抗8 mg/kg（第1、15天）和紫杉醇80 mg/m 2 （第1、8、15天）治疗，28天为一周期。安全性分析纳入了所有患者（n = 6）。 结果 . 第一个周期中未发生剂量限制毒性事件。所有患者均发生≥ 1次治疗后出现的不良事件（TEAE），5例患者发生了≥ 3级TEAE。2例患者死于疾病进展。最佳总体治疗反应为疾病稳定（n = 5）和部分缓解（n = 1）。中位治疗时间分别为雷莫芦单抗12.5周（范围：11.4 ∼ 42.7周）和紫杉醇12.2周（范围：11.0 ∼ 41.0周）。单次静脉注射雷莫芦单抗8 mg/kg后，清除率约为0.017 L/小时，半衰期（ t 1/2 ）为138 ∼ 225小时，稳态分布容积（V SS ）约为3 L。 结论 . 雷莫芦单抗联合紫杉醇方案在日本进展期胃腺癌患者中耐受良好。如同预期，这些结果与既往雷莫芦单抗药代动力学研究的结果一致。 The Oncologist 2015;20:493–494